La organización en red del poder corporativo : una tipología de redes corporativas (2012)
ABSTRACT: This research arises from the interest in understanding how corporate power is organized around the world. We study the corporate power structure or corporate network when rms share directors (interlocking directorates). We analyze corporate interlock networks in various countries to empirically derive a typology of corporate networks that suggest different theories of the organization of power. We identify an “elitist” corporate network based on unity, centralization and control; and a “pluralist” corporate network based on members’ autonomy, decentralization and communication ties. The results suggest avenues of research to nd out how networks are congured and what impacts have on society.